A Demythologizing Religious Narratives: Bultmann's Approach to Hadith within Modern Theological Studies: Demitologisasi Narasi Keagamaan: Pendekatan Bultmann terhadap Hadits dalam Studi Teologi Modern - Aulia Syahna, Ananda Aprilia; Mayangsari, Putri Ayu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Research Objectives: This study investigates Bultmann's hermeneutics, particularly the concept of demythologization used to interpret myths as existential statements, and its application in the study of Hadith. The objective is to explore how Bultmann's approach can uncover existential meanings relevant to contemporary humans and compare its applicability within Islamic studies. Methodology: This research employs a descriptive-analytical-critical approach by examining various academic texts and reputable international journals published in the last ten years. A comparative analysis between Bultmann's hermeneutics and Hadith studies is conducted to assess the potential of demythologization in an Islamic context. Main Findings: The findings reveal that demythologization aids in understanding the psychological and sociological dynamics behind mythological narratives in both Christian and Islamic contexts. It allows for the reinterpretation of mythological elements in Hadith to highlight underlying existential messages without diminishing the historical value of these religious texts. Involvement: This study significantly contributes to hermeneutical literature by extending Bultmann's concept of demythologization to Islamic studies. It opens new avenues for understanding Hadith texts in ways that align with contemporary intellectual needs. Conclusion: The research concludes that Bultmann's hermeneutical approach through demythologization offers a flexible framework for understanding the spiritual and moral meanings behind myths. This approach is relevant not only in Christian theology but also in Islamic studies, enabling new understandings of religious texts that resonate with the intellectual needs of contemporary humans.